2012
DOI: 10.1620/tjem.226.177
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pramipexole, a Dopamine Agonist, on Rapid Eye Movement Sleep Behavior Disorder

Abstract: Rapid eye movement (REM) sleep behavior disorder (RBD) is parasomnia characterized by REM sleep without atonia (RWA) and elaborate motor activity in association with dream mentation. Periodic leg movement during sleep (PLMS) is observed in a large share of patients with RBD, suggesting a common pathology: dopaminergic dysfunction. This study was undertaken to evaluate the effectiveness and mechanism of action of pramipexole, a dopamine agonist, on RBD symptoms. Fifteen patients (57-75 years old) with RBD with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 18 publications
2
33
0
Order By: Relevance
“…Kumru et al 7 did not find any difference in sleep measures detected on video recordings. Sasai et al 22 reported reduced REM density, and the rate of change in RBD symptoms was positively correlated with the rate of REM density reduction. Our study reports for the first time that rotigotine increases TST and the stage 1 % of patients, which was consistent with the result that the PDSS-2 scores decreased after rotigotine treatment.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Kumru et al 7 did not find any difference in sleep measures detected on video recordings. Sasai et al 22 reported reduced REM density, and the rate of change in RBD symptoms was positively correlated with the rate of REM density reduction. Our study reports for the first time that rotigotine increases TST and the stage 1 % of patients, which was consistent with the result that the PDSS-2 scores decreased after rotigotine treatment.…”
Section: Discussionmentioning
confidence: 96%
“…In these studies, no differences were observed in sleep architecture or general sleep measure variables after treatment. 7,21,22 However, Fantini et al reported that pramipexole increased tonic, but not phasic, electromyographic activity during REM sleep, 21 and a reduction in the sleep motor behaviors was confirmed by video recording. Kumru et al 7 did not find any difference in sleep measures detected on video recordings.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A study of 14 patients demonstrated improvement in RBD in 80 % cases with reduction in REM density and PLM index but no change in RSWA [81].…”
Section: Pramipexolementioning
confidence: 95%
“…As an objective measurement of treatment efficacy, reduction in REM sleep without atonia (RWA) measured by polysomnography (PSG) was reported in previous melatonin studies 4,5 ; however, the results of our present study of ramelteon and a previous study of pramipexole indicate their efficacy in treating RBD may be independent of reduced RWA. 6,7 The RBD severity scale (RBDSS) represents a further objective measure of the severity of RBD using video-PSG; however, measurements of RBDSS differed in 60% of patients between nights 1 and 2 in the original report. 8 In a previous retrospective melatonin study and clonazepam, the visual analog scale (VAS), a simple and clear subjective scale, was used to evaluate treatment efficacy, was used by a bed partner or family member to evaluate RBD frequency and severity in daily life.…”
mentioning
confidence: 99%